2017
DOI: 10.1103/physrevb.95.134419
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of magnetism and superconductivity in separate layers of the iron-based superconductor Li1xFex(OH)Fe1y

Abstract: The magnetic properties attributed to the hydroxide layer of Li1−xFex(OH)Fe1−ySe have been elucidated by the study of superconducting and non-superconducting members of this family of compounds. Both a.c. magnetometry and muon spin relaxation measurements of non-superconductors find a magnetic state existing below ≈ 10 K which exhibits slow relaxation of magnetisation. This magnetic state is accompanied by a low temperature heat capacity anomaly present in both superconducting and nonsuperconducting variants s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In [(Li 1−x Fe x )OH](Fe 1−y Li y )Se, superconductivity below T c = 43 K coexists with ferromagnetism below 10 K [83]. The study of SC and non-SC (Li 1−x Fe x )OHFe 1−y Se suggests a glassy magnetic state, probably comprising clusters of iron ions of varying cluster sizes distributed within the lithium hydroxide layer [92].…”
Section: Crystal Structurementioning
confidence: 96%
See 1 more Smart Citation
“…In [(Li 1−x Fe x )OH](Fe 1−y Li y )Se, superconductivity below T c = 43 K coexists with ferromagnetism below 10 K [83]. The study of SC and non-SC (Li 1−x Fe x )OHFe 1−y Se suggests a glassy magnetic state, probably comprising clusters of iron ions of varying cluster sizes distributed within the lithium hydroxide layer [92].…”
Section: Crystal Structurementioning
confidence: 96%
“…Crystals 2017, 7, 167 11 of 26 (Li1−xFex)OHFe1−ySe suggests a glassy magnetic state, probably comprising clusters of iron ions of varying cluster sizes distributed within the lithium hydroxide layer [92]. …”
Section: Crystal Structurementioning
confidence: 99%
“…Figure 18 shows the χ peaks associated with the reentrant spin glass La 0.8 Sr 0.2 Mn 0.925 Ti 0.075 O 3 . Another example is the low temperature spin-glass like state that occurs due to the presence of iron in the lithium hydroxide layers of Li 1−x Fe x (OH)Fe 1−y Se [82,83]. This compound displays spin glass-like slow magnetic relaxation that persists in the presence of the superconductivity in the iron selenide layers [83].…”
Section: All Of These Approaches Gloss Over the Details Of What Is Acmentioning
confidence: 99%
“…Many researchers have explored layered binary iron chalcogenides as parent compounds to understand their intercalation chemistry and structure–property relationships. Increasing the interlayer distance and valence electron concentration by the introduction of electropositive cations such as Li + , Na + , K + , Ca 2+ , Sr 2+ , or Ba 2+ raises the T c to 30–46 K. Intercalation of LiFe­(OH) layers between FeSe layers gives rise to layered materials with magnetic ordering at ∼12 K . Superconducting critical temperatures exceeding 40 K have been achieved by displacing Fe atoms from the LiFe­(OH) layers to occupy Fe site vacancies in the selenide layers. , While superconducting phases containing alkali metals and ammonia have been reported, there are few detailed structural reports for such compounds. Clarke et al reported the first reliable crystal structure determination of Li-ammonia intercalate in FeSe with T c as high as 43 K, as well as in situ characterization of the reactions of Li/NH 3 with FeSe using X-ray and neutron diffraction .…”
Section: Introductionmentioning
confidence: 99%